Drivers of crop commercialization in central and southern Oromia, Ethiopia - Tamrat Gebiso; Mengistu Ketema; Arega Shumetie; Getachew Leggesse (Discover Food, 2023)
Abstract More than 95% of crop production in Ethiopia comes from smallholder farmers operating on a farm size of less than 2 hectares. This implies that agriculture is dominantly operated by smallholders nationally. Agricultural commercialization is believed to improve farmers’ livelihoods; hence, commercializing agriculture in Ethiopia means contributing to the smallholder farmer’s welfare. To do so, a study of participation and level of commercialization and their determinant factors is vital. Hence, this study was initiated to evaluate crop output commercialization status and its determinants in rural Ethiopia. Heckman’s two-step model was employed for the analysis. The mean commercialization index (CI) for the sample was 43.40% while 26% and 35% of households were commercially oriented and subsistent farmers respectively. The decision to participate in crop output marketing was affected by age, market distance, and instrument for the level of farm mechanization negatively. In contrast, it was affected positively by livestock size (TLU), being in mid-highland agroecology, ownership of equines, amount of annual income, and access to market information. The intensity of commercialization was positively affected by annual income, access to market information, and number of oxen; while it was negatively affected by operational land, level of crop diversification, and market distance significantly. Improving the resource endowment, and minimizing transaction costs by improving access to market centers, market information, and means of transportation can further enhance commercialization. Improving access to farm mechanization and enhancing productivity in highland areas are also issues that shall get policy and development practitioners’ focus.